2010
DOI: 10.1002/pds.2047
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of aripiprazole use and the incidence of suicide events

Abstract: In this large, multi-site study, compared with other SGA combined, aripiprazole is not associated with an increased risk of suicide events in an inception cohort of patients with ICD-9/ICD-10 codes indicative of schizophrenia or bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The difficulty of evaluating suicidal risk more explicitly is illustrated by several trials in which suicidal behaviors were rarely encountered among subjects randomized either to ziprasidone (in doses up to 160 mg/day) or to a placebo [14,78,79,80]. Ziprasidone was included among other atypical antipsychotics in a case-control study of 4000 psychotic disorder patients in Sweden, in which treatment with atypical antipsychotic drugs (including clozapine, olanzapine, and risperidone as well as ziprasidone) yielded fewer completed suicides than alternative treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty of evaluating suicidal risk more explicitly is illustrated by several trials in which suicidal behaviors were rarely encountered among subjects randomized either to ziprasidone (in doses up to 160 mg/day) or to a placebo [14,78,79,80]. Ziprasidone was included among other atypical antipsychotics in a case-control study of 4000 psychotic disorder patients in Sweden, in which treatment with atypical antipsychotic drugs (including clozapine, olanzapine, and risperidone as well as ziprasidone) yielded fewer completed suicides than alternative treatments.…”
Section: Resultsmentioning
confidence: 99%
“…However, aripiprazole has also been associated with excessive arousal, anxiety, and akathisia, which might increase suicidal risk, as has been suggested in case reports [82,83]. However, a review of clinical observations in a total of 20,489 psychotic disorder patients found rates of suicidal events associated with aripiprazole [22] to be somewhat lower than with quetiapine [33] or ziprasidone (49 per 1000 person-years), with a not significantly different overall rate of such events compared with other antipsychotics after adjustment for the effects of diagnosis, illness severity, and other treatments (HR = 0.78 [CI: 0.48–1.30]) [80]. …”
Section: Resultsmentioning
confidence: 99%
“…These plans include health maintenance, point-of-service, preferred provider organizations, and indemnity plans located across the Northeastern, Southeastern, mid-Atlantic, Midwestern, and Western regions. The HIRD has been used previously in multiple incidence cost studies [15][18].…”
Section: Methodsmentioning
confidence: 99%
“…In a large post marketing study of aripiprazole, Ulcickas et al. found that aripiprazole used for schizophrenia and bipolar disorder was not associated with increased suicidality compared to a combined group of other antipsychotics. The unadjusted rate of suicide attempts plus completion was 2.069 events per 100 patient‐years as compared to 2.399 for olanzapine, 3.233 for quetiapine, 1.969 for risperidone, and 4.852 for ziprasidone .…”
Section: Antipsychoticsmentioning
confidence: 99%